Exploring the Students’ Response of Flipped Learning through Social Networking Sites (SNSs) - Arsanti, Lutvy; Wijayanto, Agus; Suparno, Suparno (Indonesian Journal of EFL and Linguistics, 2020)
Flipped learning has developed a particular approach that facilitates the students to acquire new knowledge outside the classroom. In this digital era, it grows as technology does. MALL (Mobile Assisted Language Learning) has a vital role in supporting English language teaching implementation. It has several applications, which can be a tool to teach English. One of the applications is using Social Networking Sites (SNSs), which the students have a high interest in using it in daily life. The research is a case study that aims to investigate the students' perception of flipped learning through Social Networking Sites (SNSs) to develop their writing ability. The participants of the research are 30 English department students in the second semester. There are ten men and 20 women in the class. The data collection was from an interview and a Technology Acceptance Model (TAM) questionnaire. This research indicates that the students have more ideas to write, and they can collaborate with their friends in writing through Social Networking Sites (SNSs). The result shows that the flipped classroom's implementation through SNSs is an alternative way for teachers to facilitate the learning of EFL writing in this digital era.